Pengaruh Beauty Influencer, Electronic Word of Mouth (e-WOM), dan Brand Image terhadap Minat Beli Skincare Glad2Glow - Sufiati Sufiati; Suhaji Suhaji (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The rapid growth of the beauty industry in Indonesia has created intense competition, particularly in the skincare product category targeting the digitally active younger generation. This study aims to evaluate the influence of Beauty Influencers, Electronic Word of Mouth (E-WOM), and Brand Image on the Purchase Intent of Glad2Glow skincare products among Generation Z in Semarang. This research employs a quantitative approach with an associative research design. Data were collected through the distribution of questionnaires to 110 respondents selected using a purposive sampling technique. The data analysis techniques used include classical assumption tests and multiple linear regression analysis via SPSS software. The results show that partially, Beauty Influencer, E-WOM, and Brand Image have a significant influence on Purchase Intent. Simultaneously, these three variables are also proven to contribute to shaping consumer tendency to make a purchase. In conclusion, a strong brand image and support from digital influencers are key factors in driving the consumption intent of Glad2Glow products. Therefore, it is suggested that brand providers continue to optimize digital marketing strategies and maintain brand reputation to sustain consumer purchase intent in the future.